EMERGENCY SURGERY TO ONCOLOGICAL PATIENTS - J.R SANGINOV; Z.H. HUSEYNZODA; F.S. MANSUROV (Avicenna Tajik State Medical University, 2017)
Objective: To analyze the results of emergency surgery to oncological patients in general surgical and oncological hospitals Methods: It has analysed the results of examinations and treatments of 122 patients with complicated forms of malignant neoplasms that treated at SROC in the period from 2012 to 2016. Results: Indications for emergency surgery in 41 patients with complicated colorectal cancer were: acute intestinal obstruction - 29 (70.7%), perforation of the tumor - 6 (14.6%), bleeding - 1 (2.4%) and paraproctitis - 5 (17.2%) patients. Primarily radical operations in the volume of hemicolectomy were performed in 15 (36.6%) cases. Symptomatic operations were performed in 21 (51.2%) patients with a locally advanced process and with the presence of distant metastases. In addition, 87 cases of emergency operations were analyzed in case of complicated malignant tumours performed in 5 medical institutions of Sogd region in 2012-2016. It was found that in non-core institutions, during the primary operation, surgeons do not always perform the adequate volume of interventions. Conclusion: Among patients who received emergency surgery in Sogd region for the period of 2012-2016, the most frequent cases are complicated by colorectal cancer, stomach (gastric) cancer and tumours of reproductive system. Of the total number of observed patients (209) in 122 cases (58.4%), patients received specialized care in the Sogdian Regional Oncological Center, and in 87 cases (41.5%) in general surgical hospitals of the region. The presence of severe complications during tumour process is not a sign of non-resectable tumours, and the implementation of emergency operations in general surgery hospital has a number of drawbacks